(untitled) (Docentes 2.0 Journal, 2020)
The Adolfo López Mateos Professional Unit - IPN has a compost production plant since 1999, which generates 2,250 tons of compost per year, but does not have the capacity to process all the organic waste from each Academic Unit. Taking into account all the waste generated in UPIBI-IPN, a compost production prototype (Lombricomposta) was designed, whose objective was to reduce the ecological footprint, generated by the institution, being an environmental indicator, providing relevant data for the design of the prototype. "The ecological footprint measures the area necessary to produce the resources consumed by an average citizen of a certain community, as well as the area necessary to absorb the waste it generates, regardless of where these areas are located" (p12). carried out in the period January 2018 - December 2019, and included a structure made up of four acrylic boxes, grinding system; powered by a stationary bicycle. Composting has gained popularity in recent years, which has managed to evolve conventional compost production systems, making them interactive, motivating and inclusive, it does not require energy, it is sustainable and also promoted physical activity in the institution.